2019
DOI: 10.5586/asbp.3639
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc oxide nanoparticles on enzymatic and nonenzymatic antioxidant content, germination, and biochemical and ultrastructural cell characteristics of Portulaca oleracea L.

Abstract: This report focuses on the application of zinc oxide nanoparticles (ZnO NPs) carrying phycomolecule ligands as a novel plant growth promoter aimed at increasing the crop productivity of purslane (<em>Portulaca oleracea</em> L.). Experiments were performed under controlled greenhouse conditions using a completely randomized design with nine replications. Purslane seeds were treated with four concentrations of ZnO NPs (0, 10, 100, and 500 mg L<sup>−1</sup>) and four concentrations of bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 64 publications
(81 reference statements)
4
6
0
1
Order By: Relevance
“…Increased concentrations of AsA and phenolic compounds in tomato leaves have been reported in the present study when 25 and 50 mg/L ZnO-NPs were applied under all drought levels. These findings are consistent with those previously reported by Iziy et al [45], in which exogenous application of ZnO-NPs improved the phenolic content in Portulaca oleracea L. The significant reduction in AsA and phenols concentration and induction of MDA and H 2 O 2 in response to foliar application of 100 mg/L ZnO-NPs indicates decreases in antioxidant potential which could be due to Zn toxicity, since Zn, as a heavy metal, at this concentration, could be too high for tomato plants. Javed et al [46] studied the effect of ZnO-NPs on the phenolic content of Stevia rebaudiana and showed a marked decrease in phenols content due to treatment with 100 and 1000 mg/L NPs which results in a decrease in antioxidant activity.…”
Section: Discussionsupporting
confidence: 94%
“…Increased concentrations of AsA and phenolic compounds in tomato leaves have been reported in the present study when 25 and 50 mg/L ZnO-NPs were applied under all drought levels. These findings are consistent with those previously reported by Iziy et al [45], in which exogenous application of ZnO-NPs improved the phenolic content in Portulaca oleracea L. The significant reduction in AsA and phenols concentration and induction of MDA and H 2 O 2 in response to foliar application of 100 mg/L ZnO-NPs indicates decreases in antioxidant potential which could be due to Zn toxicity, since Zn, as a heavy metal, at this concentration, could be too high for tomato plants. Javed et al [46] studied the effect of ZnO-NPs on the phenolic content of Stevia rebaudiana and showed a marked decrease in phenols content due to treatment with 100 and 1000 mg/L NPs which results in a decrease in antioxidant activity.…”
Section: Discussionsupporting
confidence: 94%
“…Current data showed that with increased levels of NPs or BPs in the nutrient medium, POD activity decreased in pomegranate callus tissues, and these findings are consistent with earlier work that found adverse impacts of ZnONPs treatments on POD activity in purslane roots 55 . Unlike CAT activity, POD activity considerably decreased in NPs or BPs treated calli.…”
Section: Discussionsupporting
confidence: 91%
“…However, a concentration of 20 mg L −1 caused a decline in peroxidase activity. These results were similar with previous research that discovered negative effects of ZnONPs treatments on peroxidase activity in purslane roots (Iziy et al, 2019). Low activities in antioxidant enzymes at the highest ZnONPs concentration could be attributed to the accumulation of free radicals in stressed plant tissues (Malar et al, 2016).…”
Section: Discussionsupporting
confidence: 92%